System and method for dynamic multi-objective optimization of machine selection, integration and utilization - SCHALLER GERALD PETER; ROOTE MICHAEL SCOTT; FERENCE JOHN CRANDALL; NOVAK RICHARD JAMES; DISCENZO FREDERICK M; PAI RAMDAS M; JENSEN DAVID LEE; WILLIAMS BENNET RAY (2012)
The invention provides control systems and methodologies for controlling a process having one or more motorized pumps and associated motor drives, which provide for optimized process performance according to one or more performance criteria, such as efficiency, component life expectancy, safety, emissions, noise, vibration, operational cost, or the like. More particularly, the subject invention provides for employing machine diagnostic and/or prognostic information in connection with optimizing an overall business operation over a time horizon.